Device and method for detecting position of mixed crystal phase interface of InAs nanowire

By combining the tunneling effect of position-sensitive detector and MIS structure in InAs nanowire detection, the ohmic electrode and fine metal electrode are used to solve the problems of complex operation, high cost and unrepeatable samples of detection methods in the prior art. High-precision and low-cost hybrid crystal phase interface position detection is realized.

CN119245491APending Publication Date: 2025-01-03NANTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411291230.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing InAs nanowire hybrid crystal phase detection method has problems such as difficult operation, complex sample preparation, high sample destructiveness and high cost, and lacks a detection method with simple operation, high resolution and low cost.

Method used

Using the tunneling effect in position-sensitive detector and metal-insulator-semiconductor (MIS) structure, a small-layer hexagonal boron nitride film is prepared by setting ohmic electrodes and thin metal electrodes at both ends of InAs nanowires, combined with pulsed laser deposition technology. , high-sensitivity electrical detection is performed using the front and rear differential progressive electrode structure and pad pad, to avoid direct contact between InAs nanowires and metal electrodes, protect the electrodes and realize reuse.

Benefits of technology

High-precision detection of the interface position of InAs nanowire hybrid crystal phase is realized, which reduces detection cost, improves detection sensitivity and reliability of results, solves the problem that samples cannot be reused, and provides a cost-effective detection solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119245491A_ABST
    Figure CN119245491A_ABST
Patent Text Reader

Abstract

The invention discloses a device and a method for detecting the position of an InAs nanowire mixed crystal phase interface. The method is realized through a tunneling effect in a position sensitive detector and a metal-insulator-semiconductor (MIS) structure. Wherein the position sensitive detector is formed by combining a positive electrode, a negative electrode and an InAs nanowire, and the crystalline phase change of the InAs nanowire is converted into the electrical parameter change through the Ohm law. Meanwhile, the tunneling effect in a metal-insulator-semiconductor (MIS) structure is utilized, metal electrode layers are arranged in a special front-and-back differential progressive structure, and a nanometer positioning table is matched, so that the electrical parameter change sensitivity is amplified, and the detection position is more accurate. According to the device structure provided by the invention, the detection precision and sensitivity of the crystal phase interface position of the InAs nanowire are improved, so that a more reliable detection result is obtained, in addition, the structure solves the defect that a sample cannot be repeatedly detected, and the detection cost is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of quantum mechanics and nanotechnology, and in particular relates to a device and method for detecting the position of an interface of an InAs nanowire mixed crystal phase. Background Art

[0002] InAs nanowires are one-dimensional nanostructures made of indium arsenide (InAs). Their high electron mobility, narrow bandgap (approximately 0.35 eV), and significant quantum effects hold great promise for applications in electronic and optoelectronic devices. Their unique properties enable them to excel in high-frequency electronic devices, infrared detectors, photoelectric conversion devices, and quantum computing components. InAs nanowires are fabricated using methods including chemical vapor deposition (CVD), molecular beam epitaxy (MBE), and template methods, which effectively control their size and morphology. As a key material in nanotechnology and semiconductor research, InAs nanowires hold great promise for breakthroughs and innovations in electronics, optoelectronics, and quantum technologies. The crystalline phases of InAs nanowires are primarily zinc blende (ZB) and wurtzite (WZ), with their distribution and proportions depending on the growth conditions and method. The ZB structure, a cubic structure with high symmetry and few defects, typically exhibits excellent electron mobility and optical properties, making it widely used in high-performance electronic and optoelectronic devices. The WZ structure, a hexagonal structure, exhibits stronger quantum confinement and unique optical properties, making it suitable for specific optoelectronic and quantum devices. By adjusting growth conditions such as temperature, pressure, precursor concentration, and substrate type, the crystalline phase of InAs nanowires can be controlled. This crystalline phase significantly influences the performance of nanowires. While the ZB structure improves the mobility and optoelectronic performance of electronic devices, the WZ structure exhibits advantages in specific applications. Detecting and controlling the crystalline phase of InAs nanowires is key to realizing their application in various electronic and optoelectronic devices.

[0003] Methods for determining the crystalline phase of InAs nanowires include a variety of techniques, each with its own unique advantages and scope of application. High-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED) can accurately distinguish between zinc blende and wurtzite structures by directly observing the atomic arrangement and diffraction patterns of the nanowires. X-ray diffraction (XRD) is applicable to a large number of nanowire samples and determines the crystalline phase by analyzing the position and intensity of the diffraction peaks. Raman spectroscopy identifies the crystalline phase of InAs nanowires by detecting the phonon modes of the nanowires, with different structures exhibiting distinct Raman spectral signatures. Transmission electron microscopy (TEM) combined with energy dispersive spectroscopy (EDS) can not only observe the crystalline phase of nanowires but also analyze their chemical composition. High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) uses atomic number contrast imaging to distinguish the atomic arrangements of different crystalline phases. High-resolution scanning electron microscopy (HRSEM) is used to observe the surface morphology and crystalline structure of nanowires. These detection methods have disadvantages such as high operational difficulty, complex sample preparation, high sample destructiveness, and high cost. Designing a simple, high-resolution, and low-cost method for detecting mixed crystal phases of InAs nanowires has important practical significance. Summary of the Invention

[0004] Purpose of the Invention: The present invention provides a device and method for detecting the position of mixed-phase interfaces in InAs nanowires. This technology cleverly combines position-sensitive detectors with the tunneling effect in metal-insulator-semiconductor (MIS) structures to achieve highly sensitive electrical detection of crystalline phase changes.

[0005] Technical solution: The present invention provides a device for detecting the interface position of an InAs nanowire mixed crystal phase, which comprises, from top to bottom, an InAs nanowire, boron nitride, and a metal electrode;

[0006] The metal electrode is a coarse metal electrode or a fine metal electrode;

[0007] A first ohmic electrode and a second ohmic electrode are provided at both ends of the InAs nanowire, the purpose of which is to effectively conduct current and reduce the resistance between the electrode and the semiconductor.

[0008] A pad is provided on the left side of one end of the metal electrode.

[0009] Furthermore, the boron nitride was prepared using pulsed laser deposition (PLD) technology, yielding two thin, low-layer hexagonal boron nitride films of equal size. The tunneling effect at this thickness is more pronounced, allowing for a better visualization of the tunneling current. The two thin-layer hexagonal boron nitride films are a first boron nitride film and a second boron nitride film. A coarse metal electrode is fabricated on the first boron nitride film, and a fine metal electrode is fabricated on the second boron nitride film. The side of the first boron nitride film not in contact with the coarse metal electrode faces upward, and the InAs nanowires to be tested are transferred to the first boron nitride film. The introduction of boron nitride prevents direct contact between the InAs nanowires and the metal electrodes, protecting the array electrodes from wear and tear while significantly improving their durability, allowing them to remain stable and be reused during multiple transfers.

[0010] Furthermore, the pad is the detection position point. The detection point is moved from the pad pad of the rightmost electrode to each pad pad in turn. When a current mutation is detected, the sample InAs nanowire is transferred to the second boron nitride film and it is ensured that the area where the thin metal electrode is located covers the current mutation position.

[0011] Furthermore, the coarse metal electrodes are fabricated using traditional photolithography, with a minimum line width of over 1 micron. The number of electrodes is between 10 and 50, and they are arranged in a progressively shifted configuration. The fine metal electrodes are fabricated using electron beam lithography, with a line width of 10 to 50 nanometers and a number of 50 to 100, and they are arranged in a progressively shifted configuration. Two metal electrodes of the same length form a group, arranged in a staggered, parallel arrangement, one in front of the other. The length of each group increases by 3 to 5 microns from left to right, leaving sufficient space for the bonding pads, which have a line width of 2 to 3 microns. This avoids operational inconvenience caused by metal electrodes with too small line widths and extends the life of the metal electrodes.

[0012] The resistivity of sphalerite ZB is low, while that of wurtzite WZ is high, from which the position of the crystal phase interface can be determined.

[0013] The present invention also discloses a method for detecting the position of the interface of the InAs nanowire mixed crystal phase, comprising the following steps:

[0014] S1, using ohmic contact to connect metal electrodes on both sides of the InAs nanowire;

[0015] S2, using pulsed laser deposition (PLD) technology to prepare two boron nitride films;

[0016] S3, preparing a rough metal electrode on the first boron nitride film using a photolithography technique;

[0017] S4, forming a thin metal electrode on the second boron nitride film using an electron beam exposure technique;

[0018] S5, all the coarse metal electrodes and the fine metal electrodes are connected to the pads using a solder ball bump electroplating process;

[0019] S6. Place the first boron nitride film and the second boron nitride film with the sides not in contact with the array metal electrodes facing upward, and transfer the InAs nanowire sample to be tested onto the first boron nitride film;

[0020] S7. A first ohmic electrode and a second ohmic electrode are provided at both ends of the InAs nanowire, a positive voltage of 3V is applied to the first ohmic electrode and the second ohmic electrode, a detection point is placed on the pad of the rightmost electrode, and a negative voltage of 3V is applied thereto, and observation is performed using a near-field optical microscope on a nanopositioning stage. A sudden change in current is observed, and the InAs nanowire is peeled off from the first boron nitride film and transferred to the second boron nitride film. Detection is continued from right to left, and the position of the mixed crystal phase interface is finally determined, thereby completing a method for detecting the position of the mixed crystal phase interface of an InAs nanowire.

[0021] Furthermore, step S1 specifically includes the following steps:

[0022] S11: ultrasonic cleaning with isopropyl alcohol, followed by rinsing with deionized water, followed by oxygen plasma to remove surface organic contaminants;

[0023] S12: uniformly coating a layer of photoresist on the sample surface, defining an electrode pattern on the photoresist by electron beam exposure, and then developing in a developer;

[0024] S13: Etching the surface of the InAs nanowire using a diluted hydrofluoric acid solution to remove the surface oxide layer, and immediately rinsing the sample with deionized water after etching;

[0025] S14: Selecting 50-100 nm Au as the metal electrode material and depositing the metal film using magnetron sputtering;

[0026] S15: annealing at 300° C. for 30-60 minutes in an argon protective atmosphere to promote interdiffusion between the metal and the semiconductor;

[0027] S16: Use solvent acetone to remove the photoresist, and then rinse with deionized water to finally obtain ohmic electrodes with good contact performance on both sides of the InAs nanowire.

[0028] Furthermore, step S2 specifically includes the following steps:

[0029] S21: Use single crystal SrTiO3 substrate as a platform for growing Ag buffer layer and h-BN thin film;

[0030] S22: The substrate is heated to approximately 400°C by infrared laser for in-situ cleaning;

[0031] S23: growing a 40 nm thick Ag buffer layer on the substrate at a deposition rate of approximately 2 nm / min and a growth temperature of 150-200°C;

[0032] S24: Boron nitride is then deposited at 200-250° C. with a deposition rate of 0.7 nm / min to achieve a h-BN film with a thickness of 10-15 ML.

[0033] Furthermore, step S3 specifically includes the following steps:

[0034] S31: Clean the first boron nitride film with acetone and isopropyl alcohol to remove surface contaminants, and dry it in an oven;

[0035] S32: Select high-resolution photoresist SU-8 and evenly coat the photoresist on the boron nitride surface by spin coating, set the spin speed to 3000 rpm, and the time to 30-60 seconds, followed by soft baking at 80-100° C. for 2-5 minutes to remove the solvent in the photoresist;

[0036] S33: In the UV exposure machine, align the first boron nitride film coated with photoresist with a high-resolution mask containing a 1-micron electrode pattern and perform UV exposure. The exposure energy is set to 200 mJ / cm 2 The exposure time is 15-30 seconds. After exposure, the silicon wafer is immersed in SU-8 developer for 1-2 minutes and stirred to promote the development process. After completion, the silicon wafer is rinsed with deionized water and dried.

[0037] S34: The first boron nitride film after development is hard-baked at 120°C for 5 minutes to improve the etching resistance of the photoresist; then, a metal sputtering device or an evaporation device is used to deposit a 100-200nm thick layer of metal chromium on the silicon wafer. After the metal deposition is completed, the silicon wafer is immersed in acetone to strip off the photoresist, and an ultrasonic cleaner is used to assist in ensuring complete stripping, and finally an electrode with a line width of 1 micron is obtained.

[0038] Furthermore, step S4 specifically includes the following steps:

[0039] S41: First prepare and clean the second boron nitride film, then spin-coat a layer of PMMA, and bake at 150-200° C. for 1-2 minutes;

[0040] S42: Then, an electron beam exposure device is used to write a 20-nanometer electrode structure on the resist according to the design pattern;

[0041] S43: Immerse the exposed sample in isopropyl alcohol as a developer for 30 seconds to 1 minute. After development, rinse with deionized water and blow dry with nitrogen gas.

[0042] S44: then depositing a metal electrode layer by sputtering deposition;

[0043] S45: Finally, an acetone stripping process is used to remove the resist portion not covered by the metal.

[0044] Furthermore, step S6 specifically includes the following steps:

[0045] S61: Using polydimethylsiloxane (PDMS) as a transfer medium, heat at approximately 90°C for 15-30 minutes to allow the InAs nanowires to firmly adhere to the PDMS film.

[0046] S62: Transferring the h-BN layer to a temporary substrate polyethylene terephthalate (PET) film using a wet transfer technique;

[0047] S63: placing the prepared h-BN / PET layer on the surface of the InAs / PDMS combination, then heating to about 120°C with the pressure controlled at 0.5 MPa for 20-30 minutes to combine the h-BN layer with the InAs nanowires;

[0048] S64: removing the PDMS and PET films by adding solvents ethanol and acetone;

[0049] S65: Finally, thermal annealing is performed in argon at a temperature of 200-250°C for 1-2 hours, and oxygen plasma is used to clean the interface to remove residual organic matter.

[0050] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0051] (1) The new two-dimensional material hexagonal boron nitride was introduced, which has excellent electrical insulation and interface properties. It acts as an insulator in the metal-insulator-semiconductor (MIS) structure and avoids direct contact between InAs nanowires and metal electrodes. It not only protects the array electrodes from wear, but also significantly improves their durability, allowing the array electrodes to remain stable during multiple transfers and achieve repeated use.

[0052] (2) An innovative front-to-back differential progressive electrode arrangement structure is used to detect the crystal phase interface at any position between the maximum width of the coarse and thin electrodes, which greatly improves the detection accuracy. A pad is connected to the end of each electrode to avoid the operational inconvenience caused by the small width of the metal electrode and to extend the service life of the metal electrode.

[0053] (3) The present invention combines a position-sensitive detector with the tunneling effect under the MIS structure. The tunneling current generated by the tunneling effect further amplifies the changing relationship between current and resistance, exponentially increasing it, thereby increasing the sensitivity of current changes and further improving detection accuracy.

[0054] (4) The present invention provides an innovative method for detecting the position of the interface of mixed crystal phases of InAs nanowires. This invention addresses the problems of high detection costs and the inability to repeatedly detect samples by introducing a position-sensitive detector and a metal-insulator-semiconductor (MIS) structure, thereby achieving high detection accuracy while reducing detection costs. The detector design uses a clever combination of positive and negative electrodes and InAs nanowires, and according to Ohm's law, the crystal phase changes of the nanowires are converted into measurable changes in electrical parameters. This method not only improves the sensitivity of detection, but also enhances the reliability of the results by precisely controlling the electrical parameters.

[0055] (5) The present invention adopts a special front-to-back differential progressive structure array metal electrode layout and combines it with a nanopositioning stage. This design not only amplifies the sensitivity of electrical parameter changes, but also significantly improves the accuracy of the detection position. This innovative device structure improves detection accuracy and ensures high reliability of the detection results. It solves the problem of sample non-reusability in traditional detection methods, significantly reduces detection costs, and provides a cost-effective, efficient, and easy-to-operate solution for the detection of InAs nanowire crystal phase interfaces. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 Schematic diagram of the structure of a method for detecting the mixed crystal phase interface of InAs nanowires according to the present invention.

[0057] Figure 2 Schematic diagram of the structure of the rough array metal electrode 3 made on the boron nitride 2-1 of the present invention

[0058] Figure 3 Schematic diagram of the structure of the thin array metal electrode 4 made on the boron nitride 2-2 of the present invention

[0059] Figure 4 This is a process flow chart of a method for detecting the position of an InAs nanowire mixed crystal phase interface of the present invention.

[0060] Figure 5 This is a diagram showing the arrangement structure of the metal electrode layer of the present invention.

[0061] Figure 6 This is a simplified diagram of the principle of the position sensitive detector of the present invention.

[0062] Figure 7 This is a graph showing how the current I of the position-sensitive detector changes with the position x of the detection point.

[0063] Figure 8 This is a graph showing the change of the InAs nanowire crystal phase flow I detected by a position sensitive detector under experimental conditions as the position x of the detection point changes.

[0064] Figure 9 is a graph showing the tunneling current density changing with the electric field strength in the insulator.

[0065] Figure 10 This is a graph showing how the electric field strength in an insulator changes with applied voltage.

[0066] The numbers in the accompanying drawings are: InAs nanowire-1, boron nitride-2, coarse metal electrode-3, fine metal electrode-4, first ohmic electrode-5, second ohmic electrode-6, pad-7, first boron nitride film 2-1, second boron nitride film 2-2. DETAILED DESCRIPTION

[0067] The technical solution of the present invention will be further described below with reference to the accompanying drawings.

[0068] The working principle of the method for detecting the interface position of InAs nanowire mixed crystal phase of the present invention is:

[0069] A position sensitive detector (PSD) is a device capable of detecting photoelectric position and is widely used in position sensors combined with light sources. PSDs are a type of optical sensor, also known as coordinate photocells. They convert target spatial information into an electrical signal output that matches the detector's characteristics. Based on their operating principle, detectors can be categorized as classic semiconductor detectors, novel semiconductor detectors, and thermal detectors. This invention innovatively introduces a novel structure for a position sensitive detector. Electrodes are connected to the ends of an InAs nanowire via ohmic contacts. The electrodes are made of Au, a material with high electrical conductivity that effectively conducts current and reduces the resistance between the electrode and the semiconductor. Au also exhibits excellent interfacial properties, forming a stable ohmic contact with low contact resistance. A positive voltage is applied to both sides of the electrodes, and a negative voltage is applied below the InAs nanowire. Due to the potential difference, two currents are generated within the InAs nanowire, flowing from each end of the nanowire to converge at the negative voltage point below the nanowire. At this point, a current probe is applied at the negative voltage point to measure the sum of the currents at both ends. InAs nanowires are composed of a mixture of zinc blende ZB and wurtzite WZ. Different crystal phases represent different electrical properties. Zinc blende ZB has a low resistivity, while wurtzite WZ has a high resistivity. If the InAs nanowire is regarded as a uniform linear resistor, the relationship between the detection point position x and the current I at that point can be calculated according to Ohm's law, as follows: Figure 6 The specific derivation process is as follows: Assume that forward voltage is connected on both sides of InAs Connect a negative voltage to the lower detection point The resistance of the InAs nanowire is R and its length is L, then From this we can draw the function graph of x and I, such as Figure 7 When R changes, the rate of change of the function graph will also change. If the resistivity of sphalerite is low, its resistance value is large; if the resistivity of wurtzite WZ is high, its resistance is small. Therefore, the function graph of current I and detection point position x can be obtained, as shown in the figure below: Figure 8 By observing the jump in the slope of the function graph, the interface position of the mixed crystal phase can be determined, and the specific positions of different crystal phases can also be determined.

[0070] The metal-insulator-semiconductor (MIS) structure is an important structure in modern electronic devices, and its application range is wide, including in the fields of metal-oxide-semiconductor field-effect transistors (MOSFETs), non-volatile memories and sensors. The tunneling effect, as a phenomenon in quantum mechanics, refers to the ability of particles to pass through potential barriers that are considered insurmountable in classical mechanics. The study of the tunneling effect in the MIS structure provides a new direction for the development of semiconductor devices. In order to further optimize the detection results of position-sensitive detectors, the present invention innovatively combines the change of tunneling current with the determination of the position of the mixed crystal phase interface. By introducing the tunneling current, the current increases exponentially with the change of current, which greatly improves the determination accuracy of the mixed crystal phase interface position of InAs nanowires. In the metal-insulator-semiconductor (MIS) structure, the detection sample InAs nanowire is used as a semiconductor. Due to the excellent electrical insulation and interface properties of hexagonal boron nitride (h-BN), it has become the only choice for the insulator in the MIS structure of the present invention. After many tests, the present invention selects a few layers of hexagonal boron nitride. At this thickness, the tunneling effect that occurs is the FN tunneling model. At this time, the tunneling effect is more obvious, thereby better showing the size of the tunneling current. The purpose of introducing boron nitride is to prevent the InAs nanowires from making direct contact with the metal electrodes. It not only protects the array electrodes from wear, but also significantly improves their durability, allowing the array electrodes to remain stable during multiple transfers and achieve reuse. The present invention also arranges the metal electrodes in a front-to-back differential progressive structure, and connects a pad to one side of each electrode, wherein the front-to-back differential progressive structure is as follows. Figure 5, two metal electrodes of the same length form a group, and are arranged in a staggered parallel manner, one in front and one behind, with the length of each group of electrodes increasing by 3-5 microns from left to right. The array metal electrodes include two specifications, coarse and fine, coarse array metal electrodes and fine array metal electrodes. The coarse array metal electrodes are prepared by traditional photolithography technology, with a minimum line width of 1 micron and a number of 10-50 electrodes. The specific number can be set to a larger value according to actual measurement requirements, as long as it is not greater than the maximum size of the traditional photolithography board; the fine array metal electrodes are prepared by electron beam exposure technology, with a line width of 10-50 nanometers and a number of 50-100 electrodes, thereby realizing the detection of the crystal phase interface at any position between the minimum line width of the fine electrode (4) and the maximum total width of the coarse electrode (3). The magnitude of the tunneling current in the MIS structure is positively correlated with the electric field strength on both sides of the insulating layer, such as Figure 9 , and the electric field strength on both sides of the insulating layer is positively correlated with the voltage on both sides of the insulating layer, such as Figure 10 The crystal phase changes at different positions of the InAs nanowires bring about changes in resistance, thereby changing the voltage on both sides of the insulating layer. Therefore, the tunneling current under the MIS structure not only amplifies the current in the position-sensitive detector, but also changes with the change of the crystal phase, exponentially expanding the change of current with resistance. Then, by matching coarse-gauge array metal electrodes and fine-gauge array metal electrodes, with the help of a nanopositioning stage and an optical near-field microscope, the position of the mixed crystal phase interface of the InAs nanowire can be precisely located.

[0071] Example 1:

[0072] See Figure 1In this embodiment, a method for detecting the position of the interface of an InAs nanowire mixed crystal phase is provided. The device structure, from top to bottom, comprises an InAs nanowire 1, a boron nitride 2, and a metal electrode. A first ohmic electrode (left) 5 and a second ohmic electrode (right) 6 are provided at both ends of the InAs nanowire 1; a pad 7 is provided on the left side of the end of one end of the metal electrode. The ohmic electrodes 5 and 6 are connected to both ends of the InAs nanowire 1 through ohmic contacts. The boron nitride 2 is prepared using pulsed laser deposition (PLD) technology, and two pieces 2-1 and 2-2 of few-layer hexagonal boron nitride of the same size are prepared using this method. Two sets of array metal electrodes are used, the first set of array metal electrodes consisting of coarse metal electrodes 3, and the second set of array metal electrodes consisting of fine metal electrodes 4. The coarse metal electrodes 3 are prepared using traditional photolithography technology, with a minimum line width of more than 1 micron and a number of 10-50 electrodes. The specific number can be set according to actual measurement requirements, and the electrodes are arranged in a progressive structure with front-to-back differences. Two metal electrodes of the same length form a group and are arranged in a staggered parallel manner, one in front of the other. The length of each group of electrodes increases by 3 microns from left to right. The fine metal electrodes 4 are prepared using electron beam exposure technology, with a line width of 10-50 nanometers and a number of 50-100 electrodes. The arrangement structure is the same as that of the coarse metal electrodes 3, thereby realizing the detection of the crystal phase interface at any position between the minimum line width of the fine metal electrode 4 and the maximum total width of the coarse metal electrode 3. A pad 7 with a line width of 2 microns is connected to the left side of the end of each metal electrode. A first set of array metal electrodes is made on the first boron nitride film 2-1, and a second set of array metal electrodes is made on the second boron nitride film 2-2. The side of the first boron nitride film 2-1 that is not in contact with the coarse-gauge array metal electrode is facing upward, and the InAs nanowire sample to be tested is transferred to the first boron nitride film 2-1. The pad 7 is the detection point. The detection point is moved from the pad 7 of the rightmost electrode to each pad 7 in sequence. When a current jump is detected, the sample InAs nanowire 1 is transferred to another second boron nitride film 2-2, ensuring that the area of ​​the second set of array metal electrodes covers the current jump location. The detection point is again slid from the rightmost pad 7 to the left in sequence until a current jump occurs.

[0073] Example 2:

[0074] The process flow of a method for detecting a mixed crystal phase of an InAs nanowire 1 in this embodiment includes the following steps:

[0075] S1: Metal electrodes 4 and 5 are connected to both sides of the InAs nanowire 1 using ohmic contacts. The specific preparation steps include:

[0076] S11: Ultrasonic cleaning with isopropyl alcohol followed by rinsing with deionized water. Oxygen plasma is then used to remove organic contaminants from the surface.

[0077] S12: A layer of photoresist is uniformly applied to the sample surface. Electron beam exposure is used to define an electrode pattern on the photoresist, which is then developed in a developer.

[0078] S13: etching the surface of the InAs nanowire 1 using a diluted hydrofluoric acid solution to remove the surface oxide layer, and immediately rinsing the sample with deionized water after etching;

[0079] S14: Selecting 50-100 nm Au as the metal electrode material and depositing the metal film using magnetron sputtering;

[0080] S15: annealing at 300° C. for 30 minutes in an argon protective atmosphere to promote interdiffusion between the metal and the semiconductor;

[0081] S16: Use solvent acetone to remove the photoresist, and then rinse with deionized water, and finally obtain ohmic electrodes with good contact performance on both sides of the InAs nanowire 1.

[0082] S2: Two 10ML thick hexagonal boron nitride 2 sheets were prepared using pulsed laser deposition (PLD). The specific preparation steps are as follows:

[0083] S21: Use commercial single-crystal SrTiO3(001) substrate as a platform for growing Ag(111) buffer layer and h-BN thin film;

[0084] S22: The substrate is heated to approximately 400°C by infrared laser for in-situ cleaning;

[0085] S23: growing a 40 nm thick Ag(111) buffer layer on the substrate at a deposition rate of about 2 nm / min (about 9.4 ML / min) and a growth temperature of 150°C;

[0086] S24: Boron nitride is then deposited at 200° C. with a deposition rate of 0.7 nm per minute (about 2 ML / min) to achieve a 10 ML thick h-BN film, i.e., 3.56 nm.

[0087] S3: Then, a total of 20 electrodes 3 with a line width of 1 micron are prepared on the boron nitride 2 using conventional photolithography technology. The specific preparation steps are as follows:

[0088] S31: Clean the first boron nitride film 2-1 with acetone and isopropyl alcohol to remove surface contaminants, and dry it in an oven;

[0089] S32: Select high-resolution SU-8 photoresist and evenly apply it to the boron nitride surface by spin coating at a speed of 3000 rpm for 30 seconds. Then soft bake at 95°C for 2 minutes to remove the solvent in the photoresist.

[0090] S33: In a UV exposure machine, align the first boron nitride film 2-1 coated with photoresist with a high-resolution mask containing a 1-micron electrode pattern and perform UV exposure. The exposure energy is set to 200 mJ / cm 2 The exposure time was 15 seconds. After exposure, the silicon wafer was immersed in SU-8 developer for 1 minute, and gently stirred to promote the development process. After completion, the silicon wafer was rinsed with deionized water and dried.

[0091] S34: The developed first boron nitride film 2-1 is hard-baked at 120°C for 5 minutes to improve the photoresist's etching resistance. Subsequently, a 100nm thick layer of chromium is deposited on the silicon wafer using a metal sputtering or vapor deposition system. After metal deposition, the silicon wafer is immersed in acetone to strip the photoresist. Ultrasonic cleaning is used to ensure complete stripping, ultimately resulting in an electrode with a line width of 1 micron.

[0092] S4: A total of 50 electrodes 4 with a line width of 20 nanometers are formed on the second boron nitride film 2-2 using electron beam exposure technology. The specific preparation steps are as follows:

[0093] S41: First prepare and clean the second boron nitride film 2-2, then spin-coat a layer of PMMA, and bake at 170°C for 1-2 minutes.

[0094] S42: Then, an electron beam exposure device is used to write a 20-nanometer electrode structure on the resist according to the design pattern;

[0095] S43: Immerse the exposed sample in isopropyl alcohol developer. The development time is typically 30 seconds to 1 minute. After development, rinse with deionized water and blow dry with nitrogen.

[0096] S44: then depositing a metal electrode layer by sputtering deposition;

[0097] S45: Finally, an acetone stripping process is used to remove the resist portion not covered by the metal.

[0098] S5: All the coarse metal electrodes 3 and the fine metal electrodes 4 are connected to the pads 7 with a line width of 2 microns using a solder ball bump electroplating process;

[0099] S6: Then, the two boron nitride films 2 are placed with the sides not in contact with the array metal electrodes facing upwards, and the InAs nanowires to be tested are transferred onto the first boron nitride film 2-1. The specific transfer steps are as follows:

[0100] S61: Using polydimethylsiloxane (PDMS) as a transfer medium, the InAs nanowires were firmly attached to the PDMS film at 90 °C for 15 min.

[0101] S62: Transferring the h-BN layer to a temporary substrate polyethylene terephthalate (PET) film using a wet transfer technique;

[0102] S63: placing the prepared h-BN / PET layer on the surface of the InAs / PDMS combination, then heating to 120°C, controlling the pressure at 0.5 MPa, and controlling the time at 20 minutes to combine the h-BN layer with the InAs nanowires;

[0103] S64: removing the PDMS and PET films by adding solvents ethanol and acetone;

[0104] S65: Finally, thermal annealing is performed in argon at 220°C for 1.5 hours. Oxygen plasma is used to clean the interface to remove residual organic matter.

[0105] S7: Apply a 3V positive voltage to the ohmic electrode 4 and the ohmic electrode 5, place the detection point on the pad 7 of the rightmost electrode, and connect it to a 3V negative voltage. Observe through a near-field optical microscope on the nanopositioning stage, and observe a sudden change in current. Peel off the InAs nanowire 1 from the first boron nitride film 2-1 and transfer it to the second boron nitride film 2-2. Continue to detect from right to left, and finally determine the position of the mixed crystal phase interface, thereby completing a method for detecting the position of the mixed crystal phase interface of InAs nanowires.

[0106] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A detection device for the position of the interface of InAs nanowire mixed crystal phase, characterized in that: From top to bottom, it includes InAs nanowires (1), boron nitride (2) and metal electrodes; The metal electrode is a coarse metal electrode (3) or a fine metal electrode (4); A first ohmic electrode (5) and a second ohmic electrode (6) are provided at both ends of the InAs nanowire (1); A pad (7) is provided on the left side of one end of the metal electrode.

2. The detection device for the position of the interface of the InAs nanowire mixed crystal phase according to claim 1, characterized in that: The boron nitride (2) is prepared by pulsed laser deposition (PLD) technology, and two few-layer hexagonal boron nitride films of the same size are prepared by this method; the two few-layer hexagonal boron nitride films are a first boron nitride film (2-1) and a second boron nitride film (2-2); a coarse metal electrode (3) is made on the first boron nitride film (2-1), and a fine metal electrode (4) is made on the second boron nitride film (2-2); the side of the first boron nitride film (2-1) that is not in contact with the coarse metal electrode (3) faces upward, and the InAs nanowire sample to be tested is transferred to the first boron nitride film (2-1).

3. The detection device for the position of the interface of the InAs nanowire mixed crystal phase according to claim 2, characterized in that: The pad (7) is the detection point. The detection point is moved from the pad (7) of the rightmost electrode to each pad (7) in turn. When a current mutation is detected, the sample InAs nanowire (1) is transferred to the second boron nitride film (2-2) and it is ensured that the area where the thin metal electrode (4) is located covers the current mutation position.

4. The detection device for the position of the interface of the InAs nanowire mixed crystal phase according to claim 1, characterized in that: The thick metal electrode (4) is prepared by conventional photolithography technology, with a minimum line width of more than 1 micron, a number of 10-50 electrodes, and a front-to-back differential progressive structure arrangement; the thin metal electrode (4) is prepared by electron beam exposure technology, with a line width of 10-50 nanometers, a number of 50-100 electrodes, and a front-to-back differential progressive structure arrangement; two metal electrodes of the same length form a group, arranged in a staggered parallel manner, one in front and one behind, and the length of each group of electrodes increases by 3-5 microns from left to right, leaving enough space for the pad (7), and the line width of the pad (7) is 2-3 microns.

5. The detection method for the detection device of the InAs nanowire mixed crystal phase interface position according to claim 1, characterized in that: The steps include: S1, metal electrodes are connected on both sides of the InAs nanowire using ohmic contacts; S2, using pulsed laser deposition technology PLD to prepare two boron nitride films; S3, preparing a rough metal electrode on the first boron nitride film using a photolithography technique; S4, preparing a thin metal electrode on the second boron nitride film using an electron beam exposure technique; S5, connecting all the coarse metal electrodes and the fine metal electrodes to the pads by using the solder ball bump plating process; S6, facing upward the first boron nitride film and the second boron nitride film on the sides not in contact with the array metal electrode, and transferring the InAs nanowire sample to be tested onto the first boron nitride film; S7. A first ohmic electrode and a second ohmic electrode are provided at both ends of the InAs nanowire, a 3V positive voltage is applied to the first ohmic electrode and the second ohmic electrode, a detection point is placed on the pad of the rightmost electrode, and a 3V negative voltage is applied, and observation is performed on a nanopositioning stage through a near-field optical microscope, and a current mutation is observed. The InAs nanowire is peeled off from the first boron nitride film and transferred to the second boron nitride film, and detection is continued from right to left to finally determine the position of the mixed crystal phase interface, thereby completing a method for detecting the position of the mixed crystal phase interface of an InAs nanowire.

6. The detection method for the detection device of the InAs nanowire mixed crystal phase interface position according to claim 5, characterized in that: Step S1 specifically includes the following steps: S11: ultrasonic cleaning with isopropyl alcohol, followed by rinsing with deionized water, followed by oxygen plasma to remove surface organic contaminants; S12: uniformly coating a layer of photoresist on the surface of the sample, defining an electrode pattern on the photoresist by electron beam exposure, and then developing in a developer; S13: using a diluted hydrofluoric acid solution to etch the surface of the InAs nanowire to remove the surface oxide layer, and immediately rinsing the sample with deionized water after etching; S14: selecting 50-100 nm Au as the metal electrode material and depositing the metal film using magnetron sputtering; S15: annealing at 300° C. for 30-60 minutes in an argon protective atmosphere to promote interdiffusion between metal and semiconductor; S16: Use solvent acetone to remove the photoresist, and then rinse with deionized water to finally obtain ohmic electrodes with good contact performance on both sides of the InAs nanowire.

7. The detection method for the detection device of the InAs nanowire mixed crystal phase interface position according to claim 5, characterized in that: Step S2 specifically includes the following steps: S21: Use single crystal SrTiO3 substrate as a platform for growing Ag buffer layer and h-BN film; S22: The substrate is heated to about 400°C by infrared laser for in-situ cleaning; S23: growing a 40 nm thick Ag buffer layer on the substrate at a deposition rate of about 2 nm / min and a growth temperature of 150-200° C.; S24: Boron nitride is then deposited at 200-250° C. with a deposition rate of 0.7 nanometers per minute to achieve a 10-15 ML thick h-BN film.

8. The detection method for the detection device of the InAs nanowire mixed crystal phase interface position according to claim 5, characterized in that: Step S3 specifically includes the following steps: S31: Cleaning the first boron nitride film with acetone and isopropyl alcohol to remove surface contaminants, and drying in an oven; S32: selecting high-resolution photoresist SU-8, and evenly coating the photoresist on the surface of the boron nitride by spin coating, setting the spin speed to 3000 rpm for 30-60 seconds, and then soft baking at 80-100° C. for 2-5 minutes to remove the solvent in the photoresist; S33: In the UV exposure machine, align the first boron nitride film coated with photoresist with a high-resolution mask containing a 1-micron electrode pattern and perform UV exposure. The exposure energy is set to 200 mJ / cm 2 The exposure time is 15-30 seconds. After exposure, the silicon wafer is immersed in SU-8 developer for 1-2 minutes and stirred to promote the development process. After completion, the silicon wafer is rinsed with deionized water and dried; S34: The first boron nitride film after development is hard-baked at 120°C for 5-10 minutes to improve the etching resistance of the photoresist; then, a metal sputtering device or an evaporator is used to deposit a 100-200nm thick metal chromium on the silicon wafer. After the metal deposition is completed, the silicon wafer is immersed in acetone to strip off the photoresist, and an ultrasonic cleaner is used to assist in ensuring complete stripping, and finally an electrode with a line width of 1 micron is obtained.

9. The detection method for the detection device of the InAs nanowire mixed crystal phase interface position according to claim 5, characterized in that: Step S4 specifically includes the following steps: S41: first prepare and clean the second boron nitride film, then spin coat a layer of PMMA, and bake at 150-200°C for 1-2 minutes; S42: Then, an electron beam exposure device is used to write a 20-nanometer electrode structure on the resist according to the design pattern; S43: immersing the exposed sample in a developer solution of isopropyl alcohol for a developing time of 30 seconds to 1 minute. After developing, rinsing with deionized water and drying with nitrogen gas; S44: then depositing a metal electrode layer by sputtering deposition; S45: Finally, an acetone stripping process is used to remove the resist portion not covered by the metal.

10. The detection method for the detection device of the InAs nanowire mixed crystal phase interface position according to claim 5, characterized in that: Step S6 specifically includes the following steps: S61: Use polydimethylsiloxane (PDMS) as a transfer medium at about 90°C for 15-30 minutes to firmly attach the InAs nanowires to the PDMS film; S62: Transferring the h-BN layer to a temporary substrate polyethylene terephthalate (PET) film using a wet transfer technique; S63: placing the prepared h-BN / PET layer on the surface of the InAs / PDMS combination, and then heating to 120° C., with the gas pressure controlled at 0.5 MPa, for 20-30 minutes to combine the h-BN layer with the InAs nanowires; S64: removing the PDMS and PET films by adding solvents ethanol and acetone; S65: Finally, thermal annealing is performed in argon gas with the temperature set at 200-250°C for 1-2 hours, and oxygen plasma is used to clean the interface to remove residual organic matter.